Cryptic diversity of mudskipper genus Boleophthalmus (Gobiiformes: Oxudercidae) from the north coast of East Java, Indonesia - FAIZAH NUR SHABRINA; KUNTO WIBOWO; TUTY ARISURYANTI (Society for Indonesian Biodiversity, 2024)
Abstract. Shabrina FN, Wibowo K, Arisuryanti T. 2024. Cryptic diversity of mudskipper genus Boleophthalmus (Gobiiformes: Oxudercidae) from the north coast of East Java, Indonesia. Biodiversitas 25: 412-420. Mudskippers of genus Boleophthalmus are commonly found in the Indo-Pacific area. This study aimed to examine the diversity of the genus Boleophthalmus from the north coast of East Java Province, Indonesia by employing the mitochondrial COI gene for DNA barcoding and morphological characterization. Ten individuals of this genus were analyzed. According to the similarity percentage evaluated using Basic Local Alignment Search Tool (BLAST) and Barcode of Life Data (BOLD) identification engines, all the individuals were identified as Boleophthalmus boddarti Pallas, 1770. However, phylogenetic analysis revealed that three of the individuals were identified as B. boddarti, and seven were identified as Boleophthalmus pectinirostris Linnaeus, 1758 originated from East Java, which is separated from the clade of B. pectinirostris from East Asia population. These results were supported by the genetic distance of 8.93%-13.81% and the morphological characteristics determined by principal component analysis (PCA). PCA revealed that B. boddarti and B. pectinirostris are primarily distinguished by the number of (longitudinal) scales (69-75 versus 113-123), length of second dorsal fin base (42.3-43.9 versus 38.1-49.0), and caudal fin length (18.1-22.4 versus 17.5-21.6). Further detailed studies are needed to clarify whether the seven individuals belonging to B. pectinirostris complex should be regarded as a new species or a new subspecies.